Stability and thermal conductivity of low concentration titania nanofluids / Azadeh Ghadimi - Azadeh, Ghadimi (2013)
Nanofluid as a new engineering medium is proved to be potential in many cooling processes in engineering applications. Nanofluid is prepared by dispersing nanoparticles or nanotubes in a host fluid. In this research, the “stability of nanofluids” is discussed as it has a major role in heat transfer enhancement for further possible applications. It also represents general stabilization methods as well as various types of instruments for stability inspection. Characterization, analytical models and measurement techniques of nanofluids after preparation by two-step method are studied. Low concentration TiO2/Water nanofluid was prepared by Two-step method with the stability aiding tools of sodium Dodecyl Sulfate (SDS) as anionic surfactant, pH control and ultrasonic processes. The stability of prepared nanofluids was verified by TEM, UV-vis spectrophotometer, Dynamic Light Scattering (DLS), Zeta potential, sedimentation balance method and photo capturing. In addition, characteristic measurements including thermal conductivity were carried out to consider the effect of stability on enhancement of heat transfer. The results showed that SDS addition to the nanosuspension will increasingly improve the stability of titania nanosuspension specifically for long term applications. The sedimentation rate decreases with the aid of ultrasonic processes. Central composite design (CCD) and Box Behnken design (BBD) along with response surface method (RSM) were applied to model and optimize the stability of operating variables viz. SDS correspondingly. The stability and characteristics parameters were optimized by the statistical software of Design Expert (v.8). The appropriate measurement time for clear detection of the stability by UV-vis spectrophotometer were investigated in the intervals of one day, two days, one week and one month after preparation. The obtained results revealed that after one day this inspection is not convincing for stability measurement. It was found that homogeneous nanosuspension for long term application located at surfactant loading equal to twice the amount of nanoparticle loading (0.09%wt.) for fully covering the particles at low pH value (=10). Meanwhile, the nanofluid characteristic (thermal conductivity) was evaluated in accordance with stability measurement. Quadratic models have been developed for the four responses (zeta potential, particle size, UV absorption and thermal conductivity) indicated the optimum conditions is SDS dosage of 0.04%wt. at pH value of 11.4. The study demonstrated that high thermal conductivity obtained with almost stable nanofluid in low SDS concentration and high pH value. Besides, large particle size in the optimum point demonstrated that clustering theory could be the main reason to this phenomenon. The influence of horn ultrasonic duration and power were studied by volume concentration increment. The results revealed that the optimum point which was evaluated by extra runs confirmed that the amplitude of 75% for ultrasonic horn, duration of 20 minutes and nanoparticle loading of 0.86 %vol. is the best combination of factors to reach the stable and high thermally conductive fluid. In this thesis, the major factor for thermal conductivity enhancement in nanofluids was known as the formations of nano-clusters. Therefore, by optimizing the combination of factors with Design of Experiment software in nanofluid preparation, it is expected to provide better cooling solution than the conventional cooling fluids.